Intracellular compartmentation of CTP synthase in Drosophila. - Liu, J (Elsevier, 2010)
Compartmentation is essential for the localization of biological processes within a eukaryotic cell. ATP synthase localizes to organelles such as mitochondria and chloroplasts. By contrast, little is known about the subcellular distribution of CTP synthase, the critical enzyme in the production of CTP, a high-energy molecule similar to ATP. Here I describe the identification of a novel intracellular structure containing CTP synthase, termed the cytoophidium, in Drosophila cells. I find that cytoophidia are present in all major cell types in the ovary and exist in a wide range of tissues such as brain, gut, trachea, testis, accessory gland, salivary gland and lymph gland. In addition, I find CTP synthase-containing cytoophidia in other fruit fly species. The observation of compartmentation of CTP synthase now permits a broad range of questions to be addressed concerning not only the structure and function of cytoophidia but also the organization and regulation of CTP synthesis.